2013
DOI: 10.1530/eje-12-0685
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of salivary cortisol in the diagnosis of hypercortisolism: comparison with serum and urinary cortisol

Abstract: Objective: Several tests have been proposed to diagnose patients with Cushing's syndrome (CS). The aims of the study were: i) to evaluate the performance of salivary cortisol (SC) in hypercortisolism and ii) to compare SC with serum cortisol (SeC) and urinary cortisol. Design and patients: This was a diagnostic study. Twenty-seven patients with untreated Cushing's disease (CD untr), 21 women consuming oral contraceptive pill (OCP), 18 pregnant women, and 89 healthy subjects (controls) were enrolled. Methods: S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 39 publications
4
37
0
6
Order By: Relevance
“…18 In contrast to another study, 1 we did not find any gender differences in salivary cortisol values, probably because our volunteers included individuals from 20 to 88 years old, while Lederbogen et al studied only 50-69 year-old subjects. 1 As likewise reported by Manetti et al, 7 we found no differences in late-night salivary cortisol levels, in daytime cortisol rhythm, as indicated by the F 14 /F 0 ratio, or in cortisol production rate, as indicated by AUC F0àF14 , between the women of reproductive age with regular menses who collected saliva during their follicular phase and those who were on estrogen-progestin therapy. In view of the fact that salivary cortisol reflects the free fraction of the hormone, saliva testing could be a particularly useful tool in the clinical setting in which cortisol-binding globulin is elevated.…”
Section: F0àf14supporting
confidence: 88%
See 1 more Smart Citation
“…18 In contrast to another study, 1 we did not find any gender differences in salivary cortisol values, probably because our volunteers included individuals from 20 to 88 years old, while Lederbogen et al studied only 50-69 year-old subjects. 1 As likewise reported by Manetti et al, 7 we found no differences in late-night salivary cortisol levels, in daytime cortisol rhythm, as indicated by the F 14 /F 0 ratio, or in cortisol production rate, as indicated by AUC F0àF14 , between the women of reproductive age with regular menses who collected saliva during their follicular phase and those who were on estrogen-progestin therapy. In view of the fact that salivary cortisol reflects the free fraction of the hormone, saliva testing could be a particularly useful tool in the clinical setting in which cortisol-binding globulin is elevated.…”
Section: F0àf14supporting
confidence: 88%
“…in medical conditions characterized by increased cortisol-binding globulin levels, such as during pregnancy or when estrogen-progestin contraceptives are being taken. 6,7 The aim of this study was to examine, in a community sample of adults, whether, and if so how, age, gender, metabolic syndrome and estrogen-progestin therapy affect salivary cortisol rhythm.…”
mentioning
confidence: 99%
“…Similarly, in another study performed in 15 patients in remission for at least 5 years, the persistence of visceral obesity, hypertension, impairment of glucose tolerance or diabetes mellitus, and dyslipidemia were found. Thus, patients with CS in remission might have a higher incidence of the metabolic syndrome and vascular disease, due to the persistence of an insulin resistance state and cardiac damage [49,50], but also of psychiatric disorders, compared to the general population [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Il CLU può essere determinato con metodi cromatografici (HPLC, GC-MS, LC-MS/MS), immunometrici competitivi senza estrazione, immunometrici competitivi con estrazione in fase liquida o solida, manuali (RIA, EIA) o automatizzati (CLIA) (Tab. 3) [14][15][16][17][18][19][20][21]. I metodi cromatografici, in particolare quelli in fase liquida, sono i più accurati perché in grado di separare e quantificare il cortisolo in presenza di altri steroidi anche di origine sintetica [22][23][24][25][26][27].…”
Section: Il Cortisolo Libero Urinariounclassified
“…Si conferma l'importanza di standardizzare la fase della raccolta della saliva utilizzando un dispositivo adeguato e istruzioni dettagliate per il paziente. Si ribadisce di non eseguire per lo screening della sindrome di Cushing i seguenti test: cortisolo sierico e ACTH plasmatico, prelevati casualmente nel corso della giornata, 17 …”
unclassified